A Compact Experimental Planar Antenna with a USB Connector for Mobile Phone Application - Cheng-Hung Lin; Kwong-Kau Tiong (International Journal of Antennas and Propagation)
A practical antenna design combined with a universal serial bus (USB) connector in close vicinity is proposed. In the proposed arrangement, the antenna unit consisted of two planar inverted F antennas (PIFAs) placed on the two sides of the USB connector. The antenna is located at the bottom of the mobile phone to avoid the crowded space on the top side of the phone where various mobile phone accessories are usually assigned. A diplexer is incorporated in the unit to alleviate the adverse effect of the metal USB connector on the radiating efficiency of the antenna. A prototype antenna was fabricated and tested and showed good coverage for GSM850/900/1800/1900, UMTS2100, and LTE700/2500 multibands operation. The overall performances demonstrated the good design of the proposed unit for mobile phone application.